INDIRECT SPEECH ACT ANALYSIS IN â€œIN TIMEâ€ MOVIE - rosida, ana (Study Program of English Literature, 2019)
This research is about indirect speech acts used in the movie â€œIn Timeâ€. The purpose of the research is to find out the types of used indirect speech acts. This is a qualitative research. The data cover all utterance used in â€œIn Timeâ€ movie. It is found out that there are 17 utterances which is identified as indirect speech acts. In conducting this research, the researcher watched the film, downloaded script of the movie, read the movie script, and identified the data. The researcher used Searleâ€™s theory that is indirect speech act used when the speaker wants to communicate more than what is communicate conventionally by the words he utters and classified into directive, representative, expressive, directive and commissive. The result of the study shows that there are 17 utterances that contain indirect speech acts. They are 7 representatives, 2 expressive, 7 directives, 1 commisive and declarative utterance not found in the movie. Based on the result of this research, indirect speech acts categorized into the function such as asserting, convincing, predicting, instinct, surprising, gratitude, requesting, commanding, ordering, suggesting and promising.